Diagnosis of diffuse panbronchiolitis by transbronchial lung cryobiopsy. Issue 4 (April 2023) - Ishii, Satoru; Morishita, Momoko; Matsuki, Rei; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito
Abstract: A 70-year-old man began to cough. Chest X-ray showed a tumor in the center, pleural effusion on the left side, and diffuse granular shadows on the right side. Chest computed tomography (CT) showed bronchial wall thickening and numerous granular shadows. We suspected diffuse panbronchiolitis. Thus, transbronchial lung biopsy (TBLB) and transbronchial lung cryobiopsy (TBLC) were performed. The tissue size obtained was 1 mm by TBLB and 6 mm at 5 seconds by TBLC. Histological analysis of the TBLB specimen showed lymphocyte infiltration, no fibrosis in Hematoxylin-eosin (HE) staining, and no elastic fibers in Elastica van Gieson (EVG) staining. On the other hand, TBLC specimens showed inflammatory cell infiltration and fibrosis around the bronchioles in HE staining and hypertrophy of elastic fibers in EVG staining. It was diagnosed as diffuse panbronchiolitis (DPB) from clinical and pathological findings. Cryobiopsy is useful in diagnosing DPB as well as interstitial pneumonia and lung cancer. Highlights: Diffuse panbronchiolitis (DPB) is rarely diagnosed with TBLB because of its insufficient amount of the specimen. Although the usefulness of transbronchial lung cryobiopsy (TBLC) for lung cancer and interstitial pneumonia has been widely reported, there are few reports of that for DPB so far. We hereby report a case in which TBLC was useful in diagnosing DPB as well as interstitial pneumonia and lung cancer.